The Role of Leaky Gut in Functional Dyspepsia - Wauters, Lucas; Ceulemans, Matthias; Schol, Jolien; Farré, Ricard; Tack, Jan; Vanuytsel, Tim (Frontiers in Neuroscience, 2022)
Patients with functional dyspepsia (FD) complain of epigastric symptoms with no identifiable cause. Increased intestinal permeability has been described in these patients, especially in the proximal small bowel or duodenum, and was associated with mucosal immune activation and symptoms. In this review, we discuss duodenal barrier function, including techniques currently applied in FD research. We summarize the available data on duodenal permeability in FD and factors associated to increased permeability, including mucosal eosinophils, mast cells, luminal and systemic factors. While the increased influx of antigens into the duodenal mucosa could result in local immune activation, clinical evidence for a causal role of permeability is lacking in the absence of specific barrier-protective treatments. As both existing and novel treatments, including proton pump inhibitors and pre- or probiotics may impact duodenal barrier function, it is important to recognize and study these alterations to improve the knowledge and management of FD.